Unified and distinct cognitive control deficits in adolescents with cognitive disengagement syndrome and learning burnout - Weng, Yuhan; Wu, Tingting; Wei, Yunfang; Chen, Ling; Liu, Xiqin; Cai, Kexin; Chen, Caiqi (Frontiers in Psychiatry, 2024)
Cognitive disengagement syndrome (CDS) is a psychological disorder characterized by daydreaming, mental fogginess, and slow thinking, while learning burnout (LB) is characterized by a passive and inattentive attitude toward learning. These two disorders are closely related but can be challenging to differentiate from one another. The present study aimed to identify shared and distinct cognitive control deficits between CDS and LB.We recruited 136 adolescents (aged 14 to 17 year-old) from an initial screening of CDS and LB (N = 476) and divided them into four groups: CDS, LB, CDS + LB, and typically developing control. After a second screening, 129 adolescents completed two tasks to assess their attentional networks and cognitive control capacity (CCC).Results: Adolescents with high CDS symptoms (both CDS group and CDS+LB group) exhibited impaired disengaging effect of attention and lower CCC, indicating deficits in orienting attention and the upper limit of information processing for cognitive control specifically. Furthermore, support vector machine modeling identified CCC as the most significant parameter differentiating the CDS and LB groups.Discussion: Our findings suggest that while adolescents with high CDS and high LB symptoms have similar outward manifestations in the adolescent's school life, deficits in attention and cognitive control, particularly in the CCC, may distinguish between the two groups.